TEOLOGI INKLUSIF NURCHOLISH MADJID (PEMIKIRAN TENTANG PLURALISME DAN LIBERALISME AGAMA) - Suryadi Suryadi (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
Abstract: Inclusive Theology Nurcholish Madjid (Thought About Religious Pluralism and Liberalism). Interpret the keyword Allah be ‘God’ is conflicting concepts. The question is whether the concept of God that is understood by other religions is the same as the concept of God in Islam? God in Islam, for example, childless and not begotten, whereas the God of the Christian son. God in Islam is only a temporary one  God in Hinduism  there  are three, namely  Brahma,  Vishnu and Shiva, and each  has a different role. If indeed God in Christians, Zoroastrians and others  are  the same, why the Prophet invited them  to Islam or to invite them  to the sentence sawa‘? Kalima sawa  ‘is not a theological compromise, not a common platform,  but monotheism in Islam which  became the teachings of previous  Prophets. Point of similarity is not just believe  in God, but the concept of the oneness of God brought earlier prophets and include Islam. The formulation of the problem in this research: How Nurcholish Madjid Thoughts on Religious Pluralism? And How Nurcholish  Madjid Thinking about  Religion Liberalism? Kind of research is a library (library research). The results  of this study concluded that the views Nurcholish  Madjid, basically pluralistic  society  or the nature  of pluralism,  it is not enough just with the attitude  acknowledge and accept the  fact that  the  society  is pluralistic,  but—more fundamentally—must be  accompanied by a sincere attitude  to accept pluralism  as a positive value and  the  grace  of God to man,  for it would  enrich  the  cultural growth through dynamic interaction and cross-cultural diversity. Pluralism should also not be understood merely as a “goodness negative”  (negative good),  just judging  from  its usefulness to get rid of fanaticism (to  keep fanaticism at bay). Pluralism should  be understood as “a true affinity diversity in the bonds  of civility” (genuine engagement of diversities within the bonds of civility). In fact, pluralism is a necessity for the survival of humanity, among  others,  through  the  mechanism of checks and  balances that result.  The process of liberalization and secularisation which later evolved into isms in view of Cak Nur are efforts to break away from traditional  values. The consequences of this attitude is the emergence of the notion of “personal religious Nodes: piety, resignation, sincere”. Because he let go of traditional values, the exposition does not contain  a new and fresh theory that can be useful as a remedy for the psychological plight of modern man.